Semantic Structure of the Root Word M-L-K in the Qur’an: A Lexical Semantic Analysis - Zaini, Hisyam (Study Program of Arabic Language Teaching, 2026)
This study examines the semantic structure of the Qur’anic root m-l-k (ملك) using a lexical-semantic approach. The root appears in numerous derivational forms throughout the Qur’an and is associated with concepts such as ownership, authority, kingship, sovereignty, and dominion. This study aims to identify the meanings of m-l-k and its derivations, analyze their contextual usage, and explain the semantic relations that construct the Qur’anic concept of authority and sovereignty. Employing a qualitative library research design, the study uses all Qur’anic occurrences of the root m-l-k as its research data, comprising 117 instances distributed across 21 derivational forms identified in Al-Mu‘jam al-Mufahras li Alfāẓ al-Qur’ān. These data were analyzed using a lexical-semantic framework informed by classical Arabic lexicons and contextual interpretation, with particular attention to polysemy, semantic field relations, and semantic hierarchy. The findings reveal a progressive semantic expansion from ordinary ownership (mālik) to political authority (malik), institutional sovereignty (mulk), and metaphysical dominion (malakūt). The analysis also demonstrates that the derivations form a hierarchical semantic system in which human ownership and political authority are portrayed as limited and temporary, whereas absolute sovereignty belongs exclusively to Allah. Furthermore, the study confirms that the meanings of the derivations are determined by the interaction of morphology, context, and discourse, producing an integrated semantic network encompassing theological, political, social, and metaphysical dimensions. This study contributes to Qur’anic lexical semantics by providing a comprehensive analysis of the semantic relationships among all derivational forms of the root m-l-k within a unified analytical framework.